Study of physical and chemical characteristics of cow’s milk evaporated by climbing film evaporator method - Budi Hariono; Findi Citra Kusumasari; Angga Herviona Ikhwanudin; Mokhamad Fatoni Kurnianto (AcTion: Aceh Nutrition Journal, 2024)
Cow milk is a livestock commodity that is in demand among the public as a complement to nutritional needs. Milk has various macro and micro components that support daily nutritional needs. One method to increase the nutrients contained in milk is through evaporation. The purpose of this study was to analyze the physical and chemical characteristics of milk that underwent evaporation using a climbing film evaporator. This study used an experimental method with a descriptive approach, which described the physical and chemical characteristics of cow milk before (control) and after evaporation.  The physical and chemical properties were analyzed using a paired sample t-test at the 5% level (0,05) to determine the difference in milk quality before and after the evaporation process. The temperature of the steam passing through the evaporator ranged from 132 to 1760C with an evaporation process of 25 min.  The results showed that there were significant differences (p<0,05) in freezing point, moisture content, fat, protein, lactose, minerals, and solid non-fat between fresh and evaporated milk. Density and pH showed no significant differences. Evaporation of cow's milk can enhance its nutritional content (protein, fat, lactose, and minerals).